(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
This article explores the use of word games as an effective strategy to enhance vocabulary learning. By integrating fun, competition, and meaningful context, word games actively engage learners, increase motivation, and improve vocabulary retention. Various types of word games are discussed in terms of their benefits and challenges in the classroom. While challenges such as classroom management and time constraints exist, the article concludes that with careful implementation, word games can significantly boost vocabulary acquisition and learner engagement in ESL contexts.